2022
DOI: 10.1108/ijoes-07-2021-0150
|View full text |Cite
|
Sign up to set email alerts
|

The likelihood of using crowdfunding-Waqf model in Malaysia

Abstract: Purpose This paper investigates the probability that people (prospective donors) would be willing to use the crowdfunding-Waqf model (CWM), depending on certain variables and characteristics. This study aims to develop an alternative financial model to address Malaysia’s Waqf land financing problem. Design/methodology/approach A survey study was conducted to assess the probability that people would be willing to use the CWM. This study used descriptive analysis and the logistic regression model as analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Lack of working capital and equipment shortage and other farming resources due to insufficient funds and limited access to financing sources stifle this vision. To make it worse, according to Meri Indri Hapsari, Thaker, Mohammed, and Duasa (2022), years ago, Malaysian government finance the advancement of waqf. This therefore threatens the sustainability of Waqf development because the government can not come the rescue repeatedly.…”
Section: Crowdfunding Platform As An Innovative Methods To Optimize U...mentioning
confidence: 99%
“…Lack of working capital and equipment shortage and other farming resources due to insufficient funds and limited access to financing sources stifle this vision. To make it worse, according to Meri Indri Hapsari, Thaker, Mohammed, and Duasa (2022), years ago, Malaysian government finance the advancement of waqf. This therefore threatens the sustainability of Waqf development because the government can not come the rescue repeatedly.…”
Section: Crowdfunding Platform As An Innovative Methods To Optimize U...mentioning
confidence: 99%
“…The concept of perceived usefulness, highlighted by Gangwar, Date, and Ramaswamy (2015), plays a critical role as users are only inclined to implement a technology if they observe it as beneficial in terms of efficiency, performance, and productivity for their business. Several studies, such as those conducted by Hapsari (2022) and Salim et al (2021), have indicated that performance expectancy/perceived usefulness has an impact on users' intention to use Islamic crowdfunding. This positive relationship can be attributed to the respondents' positive perception of the Islamic crowdfunding model, their knowledge of its underlying concepts and benefits, and their trust in the information provided by the online platform (Hapsari, 2022;Kazaure et al, 2020).…”
Section: Performance Expectancymentioning
confidence: 99%
“…Several studies, such as those conducted by Hapsari (2022) and Salim et al (2021), have indicated that performance expectancy/perceived usefulness has an impact on users' intention to use Islamic crowdfunding. This positive relationship can be attributed to the respondents' positive perception of the Islamic crowdfunding model, their knowledge of its underlying concepts and benefits, and their trust in the information provided by the online platform (Hapsari, 2022;Kazaure et al, 2020). Additionally, the end users believe that Islamic crowdfunding offers them direct access to investors and helps them avoid the bureaucracy of financial institutions (Salim et al, 2021).…”
Section: Performance Expectancymentioning
confidence: 99%
See 2 more Smart Citations